Factors Affecting the Implementation of STEM Education: Case Study in Vietnam - Nguyen, Nhi Thi; Thai Van, Thanh (Jurnal Pendidikan IPA Indonesia, 2025)
In recent years, STEM education has gained significant attention globally and, in particular, in Vietnam. This research aims to investigate the factors influencing the implementation of STEM education in Vietnam. This study had the objective of identifying key factors affecting the adoption of STEM education in Vietnamese schools. A survey was conducted with 865 teachers from 120 schools across Vietnam to examine these influencing factors. The methodology employed both qualitative and quantitative approaches, including surveys and data analysis to determine the impact of various factors on the successful implementation of STEM education. The results revealed that the national general education program is the most significant factor influencing STEM implementation in schools. Other contributing factors include the qualifications and awareness of teachers regarding STEM education, limited school facilities, and the content of assessment tests in teaching, all of which play important roles in the implementation process. In conclusion, this study presents recommendations and policy suggestions aimed at improving the implementation of STEM education in schools in Vietnam. The novelty of this research lies in its comprehensive examination of multiple factors influencing STEM education at the school level in Vietnam, offering new insights for educators and policymakers.